Pertumbuhan dan Hasil Tanaman Kangkung Darat pada Media Tanam Kascing dengan Takaran yang Berbeda - Indika Firmansyah; Farida Iriani; Sri Nur Widyastuti L (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTExperiments were carried out to determine the effect of vermicompost media onthe growth and yield of land kale plants located in Sukasari, Tanjungsari, Sumedang, West Java Provinces from September to October 2018. It was conducted using a randomized block design consisting of five treatments and five replications, while the treatment consisted of A = 0.0 kg vermicompost + 2.0 kg soil, B = 0.5 kg vermicompost + 1.5 kg soil, C = 1.0 kg vermicompost + 1.0 kg soil, D = 1.5 kg vermicompost + 0.5 kg soil, E = 2.0 kg vermicompost + 0 kg soil. The results showed that giving vermicompost significantly affected plant height at the age of 29 HST, 36 HST, 43 HST, root length, shoot fresh weight, fresh weight, shoot/root ratio of plant at 43 HST. The use of vermicompost at a doses 1 kg kg-1 soil given the best effect than the other doses.